Healthcare Interoperability: Breaking Down Data Silos through Automation - Peeyush Khandelwal (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article examines the transformative impact of automated systems on healthcare interoperability, focusing on the implementation of standardized data exchange protocols and their role in breaking down traditional information silos. The article explores core components including HL7, FHIR, and APIs, analyzing their collective contribution to enhanced healthcare delivery. The article investigates real-world applications in pharmacy integration and claims processing, demonstrating significant improvements in medication management, patient safety, and administrative efficiency. Through examination of implementation strategies and outcomes, the article highlights the crucial role of stakeholder collaboration, process automation, and standards adoption in achieving successful interoperability. The article reveals substantial benefits in care coordination, clinical decision support, patient engagement, and public health surveillance, establishing the fundamental importance of automated interoperability systems in modern healthcare delivery.